2005
DOI: 10.1507/endocrj.52.605
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Distribution of Somatostatin Receptor Subtypes in Human: An Immunohistochemical Study

Abstract: Abstract. Somatostatin is well known to inhibit the hormone secretion of various peptides. This action has been considered to be generally mediated via six different specific somatostatin receptors (sstr), sstr1, sstr2A, sstr2B, sstr3, sstr4, and sstr5. It then becomes very important to demonstrate the localization of these sstr subtypes in order to elucidate the possible biological and/or clinical significance of somatostatin actions. These sstr subtypes have been demonstrated to be expressed throughout the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
78
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 43 publications
(54 reference statements)
11
78
0
3
Order By: Relevance
“…Currently, 5 subtypes of somatostatin receptors have been identified in humans (SSRT1, SSRT2, SSRT3, SSRT4, SSRT5), with SSRT2 further classified into subtypes 2A and 2B [47] . Of particular interest, somatostatin receptor expression has been found in a large number of tumors, of which NETs are the archetypical class, and this forms the basis for the molecular imaging of NETs.…”
Section: Somatostatin Receptor Scintigraphymentioning
confidence: 99%
“…Currently, 5 subtypes of somatostatin receptors have been identified in humans (SSRT1, SSRT2, SSRT3, SSRT4, SSRT5), with SSRT2 further classified into subtypes 2A and 2B [47] . Of particular interest, somatostatin receptor expression has been found in a large number of tumors, of which NETs are the archetypical class, and this forms the basis for the molecular imaging of NETs.…”
Section: Somatostatin Receptor Scintigraphymentioning
confidence: 99%
“…A number of laboratories have used immunocytochemical methods to determine the pattern of SSTR expression in human islet cells (as summarized in Table 2), and similar to rodent studies the results vary, likely due to the different antibodies employed (Kumar et al, 1999;Papotti et al, 2002;Schindler et al, 1997;Schindler et al, 1998;Schulz et al, 1998;Portela-Gomes et al, 2000;Reubi et al, 1998;Gu and Schonbrunn 1997;Dournaud et al, 1996;Kimura et al, 2001;Taniyama et al, 2005). However, consistent across reports were the observations that human pancreatic A-and B-cells show a high expression of SSTR2, while striking inconsistencies remain with respect to cell-specific expression of SSTR1, SSTR3-SSTR5.…”
Section: Humansmentioning
confidence: 99%
“…Octreotide LAR has high binding affinity for the somatostatin receptor subtype SSTR2, and SSTR2 was constantly detected in many pancreatic β-cells [11]. Baldelli et al also reported that insulin levels 30 min after OGTT were significantly suppressed after the administration of octreotide LAR [12], and it is suggested that the decrease in early insulin secretion by OGTT during treatment with octreotide LAR is involved in worsening of glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%